A case study of hurdle and generalized additive models in astronomy: the escape of ionizing radiation - Hattab, Mohammad W.; Paardekooper, Jan-Pieter (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. The dark ages of the Universe end with the formation of the first generation of stars residing in primeval galaxies. These objects were the first to